Poetics in the landscape - Louw, Christelle (University of the Free State, 2020)
Climate change is a global issue and the main challenge regarding this predicament is the human being's lack in ability to protect our natural environments. This dissertation investigates how to overcome the conventional design process by critically analysing the context's geomorphology and vegetation to encourage a better understanding of the site. An interpretation centre is proposed to inform the visitors of how the site is formed and how the vegetation functions, to create awareness of nature conservation. Awareness of nature conservation will attempt to equip the visitor with empathy towards the environment in order to protect it better. Once the environmental prosesses are better understood, the visitor can aid in the conservation process. The geomorphology , fynbos and Cedar tree will be investigated in depth; poetic ideas will be derived and together with architectural theories, a piece of architecture will be developed. A main walkway that leads from the parking to the Stadsaal caves will be constantly exposed to the landscape to encourage a nature-near approach throughout the proposed design. Ideas that are derived from the context will aim to result in a unique structural approach, which metaphorically demonstrates the presence of a cave whilst overlooking the landscape. The proposed design process will make use of case and precedent studies as well as contextual analysis, where the unique Stadsaal caves that are carved t perfection by natural erosion are observed. Awareness of the natural processes on site will attempt to create a being of care among the visitors. The function of the interpretation centre will aim to form a symbiotic relationship between the landscape and itself.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2020
Keywords: Architecture; Cederberg; Fynbos; Conservation of natural resources; Ecotourism -- South Africa -- Cederberge; Conservation centre -- South Africa -- Cederberg -- Design and plans